PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN ( STUDI RUMAH MAKAN PUTI BUANA PEKANBARU) - Pratama, Robbi Satria; Gimin, Gimin; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The study aims to determine the impact of the reward and punishment on the performance of employees of Rumah Makan Puti Buana Pekanbaru. The population in this study was the entire employee of Rumah Makan Puti Buana Pekanbaru as much as 130 employees. Sample 57 taken using random sampling technique. Data is collected using a questionnaire, then analyzed by multiple linear regression methods. The results showed that there was a simultaneous influence of reward and punishment to the performance of employees of Rumah Makan Puti Buana Pekanbaru with a donation of 0.579 or 57.9%. With the equation Y =-1,324 + 0.502 + 1.127 X This research advice can be used as a reference to improve the performance of employees through the application of reward and punishment to the performance of employees of the food stalls Puti Buana.Key Words: Reward, Punishment, Employee Performance